Analisis Strategi Pemasaran Digital pada UMKM Batam Indo Keramik - Shereen, Shereen; Juniarty, Shely; Gunadi, Jacky; Sentoso, Antony; Milano, Lady (Social Engagement: Jurnal Pengabdian Kepada Masyarakat, 2023)
The rapid development of the digital era has led to intense competition between MSME’s. This encourages every business actor to innovate an new item or service to attract the attention of consumers. Business actors must be able to carry out marketing strategies on social media. The method used by researches is qualitative data, examining data directly from the source according to the circumstances that occur in the object of research. The marketing strategy applied to Batam Indo Keramik, namely direct marketing, digital marketing, promotions for wholesale purchases and provide same-day delivery facility. The form of implementation of digital marketing that is applied is in the form of WhatsApp Business, Linktree and Mailchimp with the aim to help expand market share business.